Study of blockchain's consensus mechanism based on score: An improved consensus mechanism. Issue 1 (10th May 2021) - Cai, Shaobin; Han, Tangxuan; Wang, Yuhao; Zhang, Hu
Abstract: The consensus mechanism is a key technology to achieve state consistency among distributed nodes and it determines the consensus efficiency and stability of the blockchain system. If the consensus efficiency and stability are improved, that can promote the development of the entire society. Therefore, it is necessary to improve the consensus efficiency and stability of the blockchain system. However, there are many disadvantages in the existing consensus mechanism, such as high communication complexity, low throughput, and poor scalability. For solving these disadvantages, a blockchain consensus mechanism Score‐Based Byzantine Fault Tolerance (SBBFT) is proposed. First, the score of nodes are obtained by Analytical Hierarchy Process (AHP) and SBBFT uses the score of the node to choose a node to be the primary node and acknowledgment node. Second, SBBFT selects c acknowledgment nodes to be an acknowledgment node subset. This subset can change the communication of nodes from all‐to‐all to all‐to‐ c . Moreover, the view change of acknowledgment node subset can make the system resistant to attacks from more malicious nodes. According to the experiment, 900, 000 transactions from Ethereum, the result demonstrates SBBFT can significantly reduce the communication complexity, improve the consensus efficiency and stability of the system.